Intimate Partner Sexual Violence: A Review of Terms, Definitions, and Prevalence. (July 2015) - Bagwell-Gray, Meredith E.; Messing, Jill Theresa; Baldwin-White, Adrienne
Intimate partner sexual violence (IPSV) is a significant aspect of intimate partner violence (IPV). While intimate partners commit one third of sexual assaults, IPSV is often overlooked in studies about IPV and in research on sexual violence. There are difficulties identifying, defining, and measuring IPSV, and research lacks consistency in terminology and measurement. The purpose of this article is to review the terms, definitions, and measurements associated with IPSV. Academic journals and nonscholarly documents from the United States were searched for articles and reports associated with the study of sexual violence and IPV. Forty-nine documents met the criteria for inclusion. A four-part taxonomy defining IPSV was developed, which included IPSV, intimate partner sexual coercion, intimate partner sexual abuse, and intimate partner forced sexual activity. The average weighted prevalence rates of these various forms of IPSV were calculated across included research studies. However, the measurements generally used to assess IPV do not adequately measure IPSV. Future research should consist terms to ensure consistent conceptualization and measurement of IPSV and to inform practice with survivors.